Human IgG responses against the N-terminal region of Merozoite Surface Protein 1 of Plasmodium vivax - Obando, Hernando Antonio del Portillo (1992)
ABSTRACT: The complete primary structure of the gene encoding the Merozoite Surface Protein 1 of Plasmodium vivax (PvMSP-1) revealed the existence of interspecies conserved regions among the analogous proteins of other Plasmodia species. Here, three DNA recombinant clones expressing 50, 200 and 500 amino acids from the N-terminal region of the PvMSP-1 protein were used on ELISA and protein immunoblotting assays to look at the IgG antibody responses of malaria patients from the Brasilian amazon region of Rondônia. The results showed the existance of P. vivax and P. falciparum IgG antibodies directed against PvMSP-1 antigenic determinants expressed in the clones containing the first 200 and the following 500 amino acids of the molecule, but not within the one expressing the most N-terminal 50 amino acids. Interestingly, there was no correlation between the levels of these IgG antibodies and the previous number of malaria infections. _______________________________________________________________________________ RESUMO